The time as an emergent property of quantum mechanics, a synthetic description of a first experimental approach. (June 2015) - Moreva, E; Brida, G; Gramegna, M; Giovannetti, V; Maccone, L; Genovese, M
Abstract: The ''problem of time" in present physics substantially consists in the fact that a straightforward quantization of the general relativistic evolution equation and constraints generates for the Universe wave function the Wheeler-De Witt equation, which describes a static Universe. Page and Wootters considered the fact that there exist states of a system composed by entangled subsystems that are stationary, but one can interpret the component subsystems as evolving: this leads them to suppose that the global state of the universe can be envisaged as one of this static entangled state, whereas the state of the subsystems can evolve. Here we synthetically present an experiment, based on PDC polarization entangled photons, that shows a practical example where this idea works, i.e. a subsystem of an entangled state works as a 'clock" of another subsystem.